Market Structure in the Philippine Financing Company Sector - Valderrama, Helena Agnes S. (Philippine Management Review; Vol 9 (2001), 2016)
This paper finds that qualitative information obtained from a survey on the product emphasis and clients served by financing companies show the existence of strong market segmentation in the sector.  Medium-sized and large financing companies have a different set of product offerings and clients from small financing companies.  Using profit-cost margins or return on sales as a performance indicator, statistical tests confirm at a 96.5% level of significance that the two samples do not come from the same population  The Herfindahl Index and 4-firm concentration ratio were used to quantify the degree of concentration in the financing company sector.  The study finds that as a whole, the financing company sector is highly concentrated, with 6 companies out of over 150 accounting for about 50% of the market.  The market segment consisting of medium-sized and large financing companies is oligopolistic in structure, while that of small financing companies is more competitive.  Higher price-cost margins are documented for the former subsector, strengthening the finding that the market structure of medium-sized and large financing companies is not that of perfect competition.  At least two factors are propose as explanation for the high degree of concentration in the sector: 1) economies of scale brought about by access to cheaper funds through affiliated companies, principally parent companies which are big universal banks, and 2) product differentiation due to access to a ready borrowers market.